Representasi Nilai Toleransi dalam Animasi Keluarga Somat Episode “Hari Kartini” - Budi Santoso; Irma Winingsih (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2022)
This study aims to describe representation of the value of tolerance in the animation film Somat’s Family episode "Kartini’s Day". Qualitative descriptive research method used in this study. The data is taken from the animation film Somat’s Family episode "Kartini’s Day". Research approach used  semiotics approach, especially communication semiotics from John Fieske on representation theory. Data  analysis focuses on three levels of representation, namely  level of reality, level of representation, and  level of ideology. The results show that at the level of reality tolerance is represented in the form of appearance, make-up, costumes, and behavior of the characters who respect differences. The technical representation level uses close up, two angle shots, medium shots, and long shots techniques. Bright lighting is used to indicate a happy felling of the character. The editing section uses continuity editing. The voice code consists of  dialogues of the characters. Conventional representation codes consist of characters who respect differences, actions and dialogues of characters which show respect for different cultures or opinions. At ideological level, animation series  Somat’s Family episode “Kartini Day” consist of  ideology of tolerance and respect for different cultures. The ideology of pluralism was also revealed which was then united in the concept of Bhineka Tunggal Ika.